(untitled) (Global Journal of Human-Social Science, 2022)
The icy winds of the Baltic bite deep into the bones of barely-clothed prisoners of an unnamed war camp The cold is unbearable in the frigid Prussian hinterlands the chatter minimal and everyone is huddling to survive Amidst the stale air of death and starvation small clouds of melodic choir powerfully pierce through the hushed chill Ari-rang ar-ri- rang ara-ri-yo 1 From the bellies of a group of Koryo Saram the Korean folk anthem wistfully winds its way through the barbed wires straining to reach back home